대형저서동물과 물새류 서식지인 장봉도 습지보호지역의 생태적 중요성 - 이시완(Si-Wan Lee); 김용현(Yong-Hyun Kim); 강태한(Tae-Han Kang); 송민정(Min-Jung Song) (한국조류학회지, 2010)
서해안 장봉도 습지보호지역에서 대형저서동물과 물새류의 출현양상 및 생태적 중요성을 알아보고자 대형저서동물은 2008년 6월에, 물새류는 2008년 5월과 6월에 조사하였다. 대형저서동물은총 48종/1.2㎡, 평균서식밀도 758개체/㎡로 출현하였다. 장봉도 남 ․ 북측 조간대는 니질성 퇴적상이 발달되어 저서다모류가 우세하였다. 동만도와 서만도 조간대는 사질성 퇴적상이 발달되어 단각류와 이매패류인 말백합이 우세하였다. 동물문별 출현종수는 저서다모류가 19종으로 전체 중39.6%를 차지하였으며, 그 다음으로는 갑각류, 연체동물류 순이었다. 서식밀도는 갑각류가 415개체/㎡로 54.7%의 우점율을 보였으며, 그 다음으로 저서다모류, 연체동물류 순으로 우점하였다. 장봉도 습지보호지역 전체에서 물새류는 총18종, 13,337 개체가 출현하였으며, 최우점종은 괭이갈매기이었고, 차우점종은 노랑부리백로이었다. 장봉도 습지보호지역 중에 장봉도에서는 14종 1,029개체가 관찰되었고, 동 ․ 서만도에서는 12종 12,308개체가 관찰되었다. 동·서만도에서 번식조류는 10종이 관찰되었으며, 이 중 괭이갈매기는 12,050개체가 관찰되었고, 12,000둥지가 있는 것으로 나타났다. 노랑부리백로는 장봉도 일대 갯벌에서 취식활동을 하였고, 집단 번식지인 서만도에서 31둥지가 관찰되었다. 검은머리물떼새는 동만도에서 4둥지 이상, 서만도에서는 1둥지 이상 확인되었다. 왜가리와 중대백로는 서만도 남측 교목림에서 각각 2둥지와 15둥지가 확인되었으며, 민물가마우지도 남측 교목층에서 12둥지가 확인되었다. 가마우지는 나출된 절벽에서 35둥지가 확인되었으며, 저어새 1쌍이 번식하는 것도 확인되었다. 물새가 번식지로 이용하고 있고, 주변 갯벌에 서식하고 있는 저서동물로부터 먹이원을 얻고 있는 장봉도 습지보호지역은 생태적으로 중요한 역할을하고 있다고 판단된다. 이러한 장봉도 습지보호지역은 조력 발전소 조성, 해사 채취 등의 꾸준한개발압력을 받고 있어 이에 대비한 습지보호지역의 보전 및 관리가 반드시 마련되어야 할 것이다. To recognize the ecological importance of Jangbongdo Coastal Wetland Protected Area, the appearance patterns of macro-benthic fauna and waterbirds were investigated in June 2008, and from May to June 2008, respectively. The macro-benthic fauna comprised 48 species/1.2㎡ occurring at a mean density of 758 indiv./㎡. Benthic polychaetes were the major faunal taxonomic group of the muddy sedimental face of the southern and northern tidal flat areas in Jangbongdo. On the other hand, sandy sedimental face developed in the tidal flat around Dongmando and Seomando where Amphipoda (Crustacea) and Bivalvia (Mollusca) such as Meretrix petechialis presented as the dominant faunal group. Nineteen species (39.6%) of benthic polychaetes appeared which was the highest number of species among taxonomic groups. After benthic the next two faunal groups with the highest species number were Crustacea and Mollusca. Crustaceans were sampled at 415 indiv./㎡ (54.7%), which was the most abundant faunal group. Polychaeta and Mollusca were the next two groups with the highest abundance. A total of 18species and 13,337 individuals of waterbirds were observed in Jangbong Wetland Protected Area. Approximately, 12,050 birds bred in 12,050 birds bred in Dongmando and Seomando (12,000nests) with the Black-tailed gull (Larus crassirostris) identified as a dominant species. Swinhoe's Egret (Egretta eulophotes - 31 nests in Seomando), Eurasian Oystercatcher (Haematopus ostralegus, 4 nests in Dongmando, 1 nest in Seomando), Grey Heron (Ardea cinerea, 2 nests in Seomando), Great Egret (Egretta alba, 15 nests in Seomando), Great Cormorant (Phalacrocorax carbo, 12 nests in Seomando), Temminck's Comorant (Phalacrocorax capillatus, 35 nests in Seomando) also bred on the islands. Jangbongdo tidal flat is an important habitat for rare birds. Specifically, more than 1% of the Swinhoe's Egret (Egretta eulophotes) world population use this tidal flat. Also, important birds like the Black-faced Spoonbill (Platalea minor) and the Eurasian Oystercatcher (Haematopus ostralegus) reside in the tidal flat. Benthic organisms are good prey for these birds. Jangbongdo Coastal Wetland Protected Area also has a development plan that includes such activities as sand mining, and tidal power plant construction. Thus, this area must be continuously managed and preserved for the protection of rare waterbirds. KCI Citation Count: 3